While You Are Sleeping: Marital Ambivalence and Blunted Nocturnal Blood Pressure - Birmingham, Wendy C.; Herr, Raphael; Cressman, Mikel; Patel, Neha; Hung, Man (International Journal of Environmental Research and Public Health, 2024)
Marital relationships offer health benefits, including a lower risk of cardiovascular disease (CVD). However, quality of the relationship matters; ambivalent behaviors may increase CVD risk by affecting blunted nocturnal blood pressure (BP) dipping. This study tracked daytime and nocturnal SBP and DBP in 180 normotensive individuals (90 couples; participant mean age 25.04; 91.58% white) over a 24 h period using ambulatory blood pressure monitors to explore the impact of martial quality. Results showed that perceptions of spousal ambivalence were associated with blunted nocturnal BP dipping. Perceptions of one’s own behavior as ambivalent also showed blunted nocturnal dipping. When in an ambivalent relationship, a gender interaction was found such that women were most likely to have blunted SBP dipping, but men were more likely to have blunted nocturnal DBP dipping. Overall, this study found an association between ambivalence and BP dipping, thus uncovering one virtually unexplored pathway by which marital relationships may have adverse effects on health.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ambivalence; blood pressure; nocturnal dipping; relationship quality